PROGRAM GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) TERHADAP PENINGKATAN MOTIVASI KERJA PADA KARYAWAN PT. MARUKI INTERNASIONAL INDONESIA MAKASSAR - Asrijun Juhanto; Jalil Genisa; Allaudin Al Idris (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
The Healthy Living Community Movement (Germas) is an effort to increase awareness, willingness and ability for everyone to live a healthy life in order to improve the health status of the community as high as possible. The purpose of this study was to conduct an analysis that influenced the Germas program to increase employee motivation at PT. Maruki international Indonesia Makassar. The research method is an analytic survey with a cross sectional study approach. The total population in this study were 241 employees and the sample size was 71 respondents. Collecting quantitative data using questionnaires and checklists, analyzed by univariate, bivariate and multivariate. The results showed that the Physical Activity variable had a significant effect (p=0.012<a=0.05) on the increase in work motivation, the Nutrition Improvement Variable had a significant effect (0,=0.048 <0,=0.05) on the increase in work motivation, the detection variable Early childhood has a significant effect (p=0.008<a=0.05) on increasing work motivation It is recommended with the results of this study that the relevant government and company management can provide socialization in the application of the Healthy Living Community Movement (GERMAS) program, especially in the workplace, so that healthy workers' productivity increases